Determination of interface state density of MXene and polyaniline nanocomposite/p-Si diode by advanced Fytronix amplitude method - Demirelli, Kadir; Yalcin, Mesut; Dere, Aysegul; A.Mansour, Shehab; Yakuphanoğlu, Fahrettin (Elsevier, 2026)
MXene:PANI:PbO nanocomposite was synthesized by a hydrothermal route and used to fabricate an Al/p-Si/MXene(0.06):PANI(0.02):PbO0.92/Al diode with a Ti3C2Tx MXene interfacial layer. Electrical properties were studied by IV, CV, and G-V measurements, confirming rectifying and photosensitive behavior. Impedance/admittance results show improved performance via interfacial engineering. Frequency-dependent data (100 kHz-1 MHz) and C-ADJ-G(ADJ) analysis (1-4 V) elucidated interface states and carrier dynamics.
Keywords: MXene:PANI:PbO nanocomposite; Schottky diode; Interfacial engineering; Electrical characterization; Impedance-admittance analysis